2015
DOI: 10.21608/jppp.2015.53305
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION OF SUSCEPTIBILITY AND RESISTANCE MECHANISMS OF SOME EGYPTIAN WHEAT CULTIVARS (Triticum aestivum L.) INOCULATED WITH Blumeria graminis f.sp. tritici USING CERTAIN BIOCHEMICAL, MOLECULAR CHARACTERIZATION AND SEM

Abstract: Two greenhouse experiments were conducted in the greenhouse of Agricultural Botany Department, Faculty of Agriculture, Kafrelsheikh University, Egypt, during two seasons (2012-2013 and 2013-2014) to study biochemical, molecular characterization and SEM investigation of susceptibility and resistance mechanisms of ten Egyptian wheat cultivars (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…These results might be due to the negative role of broomrape on growth characters of faba bean plants and the photosynthetic process, consequently decreasing chlorophyll concentration and relative water content. These detrimental effects of broomrape (as biotic stress factor) on the physiological parameters are similar to the effects of many other stress factors on various plants: drought stress [ 37 , 38 , 39 , 40 ], salinity stress [ 41 , 42 , 43 , 44 , 45 ] and biotic stress factors [ 46 , 47 ]. Briache et al [ 48 ] reported that Misr1 and Misr3 faba bean genotypes displayed resistance levels greater than susceptible ones; moreover, Misr1 and Misr3 gave the highest yield.…”
Section: Discussionmentioning
confidence: 64%
“…These results might be due to the negative role of broomrape on growth characters of faba bean plants and the photosynthetic process, consequently decreasing chlorophyll concentration and relative water content. These detrimental effects of broomrape (as biotic stress factor) on the physiological parameters are similar to the effects of many other stress factors on various plants: drought stress [ 37 , 38 , 39 , 40 ], salinity stress [ 41 , 42 , 43 , 44 , 45 ] and biotic stress factors [ 46 , 47 ]. Briache et al [ 48 ] reported that Misr1 and Misr3 faba bean genotypes displayed resistance levels greater than susceptible ones; moreover, Misr1 and Misr3 gave the highest yield.…”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, the plants can avoid ROS injury with upregulation of enzyme activity like catalase and polyphenol oxidase, which play vital roles in ROS scavenging [15][16][17]. Salicylic acid (SA) plays a main role under stress conditions in the regulation of photosynthesis and many physiological processes [13,18], proline metabolisms, and antioxidant defense systems as well as provides protection under abiotic stresses [19] and improves the growth characters and yield parameters of canola plant [4]. Use of SA significantly alleviated the injurious impacts of drought and decreased lipid peroxidation in wheat plants [20], increased growth characters and yield of faba bean plants, as well as improved activity of antioxidant enzymes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sugar beet needs a shorter period of productivity and consumes less water than sugarcane [ 2 , 3 ]. Many environmental stress factors affect the plant growth and productivity in various plants; biotic factors [ 4 , 5 , 6 , 7 ], salinity [ 8 , 9 , 10 , 11 ], heat [ 12 ], drought stress [ 13 , 14 , 15 ]. Drought is one of the most harmful stresses which, threat agricultural production, under drought factor, morphological characteristics such as leaves number, leaf area and stem length were decreased [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that Si is an essential element in increasing drought stress tolerance and alleviate the mineral nutrient shortage in plants [ 43 ]. Si application led to increase root and shoot biomass of tomato [ 44 ] and barley plants [ 45 ] under drought and in pepper under salinity [ 8 ]. Furthermore, Si causes an increase in chlorophyll content, RWC and postponed leaf senescence [ 46 ], also, Si can improve the activities of some essential enzymes in rice seedlings under salinity, which scavenge ROS [ 47 ] and decrease the oxidative stress of arsenic (As) on wheat seedlings [ 48 ].…”
Section: Introductionmentioning
confidence: 99%